Poetic Images, Presence, and the Theater of Kenotic Rituals - SEPSI, Enikő (Routledge Advances in Theatre & Performance Studies, 2022)
This book explores the interrelation of contemporary French theatre and poetry. Using the pictorial turn in the various branches of art and science, its observable features, and the theoretical framework of the conceptual metaphor, this study seeks to gather together the divergent manners in which French poetry and theatre address this turn. Poetry in space and theatricality of poetry are studied alongside theatre, especially to the performative aspect of the originally theological concept of ""kenosis"". In doing so the author attempts to make use of the theological concept of kenosis, of central importance in Novarina's oeuvre, for theatrical and dramatological purposes. Within poetic rituals, kenotic rituals are also examined in the book in a few theatrical practices - János Pilinszky and Robert Wilson, Jerzy Grotowski and Eugenio Barba - facilitating a better understanding of Novarina's works. Accompanied by new English translations in the appendices, this is the first English language monograph related to the French essayist, dramaturg and director Valère Novarina's theatre, and will be of great interest to students and scholars in theatre and literature studies.